Self- Representation di Era Digital (Analisis Semiotika Acara TV Black Mirror Episode Nosedive) - Clarisa Tan; Wulan Purnama Sari (Koneksi, 2019)
The rise of technology and information makes it easier for humans to communicate, introducing new aspects about the relationship between individual freedom and technology. Digital technology and social media are very influential in everyday life, communication between family and friends is not limited by geographical challenges. Social media makes it easier to express and understand ourselves through online communities. This research aims to see how self-representation in the digital era is shown through Netflix TV show Black Mirror episode Nosedive by Charlie Brooker. The reasercher conducted a semiotic analysis on the first episode in Season 3, "Nosedive," regarding the self-representation shown and how the relationship was created through social media in all Lacie Pound's relationships. Obsessed with social rankings Lacie must carry out positive interactions and represent herself according to social standards. Rating values in Nosedive make relationships between people seemed fake because they are concerned with the judgments given to each other. All people in the world must follow the existing social standards or they can be exiled because they have low rating. Nosedive mimics the real life problem of obsession with social achievement through cognitive alienation, that tells their current excitement with digital and social connectivity. This study uses Charles Sanders Pierce's semiotics theory with a qualitative research method approach. Researchers collect data by observation and documentation, library research and online sources.Munculnya teknologi dan informasi memudahkan manusia untuk berkomunikasi, memperkenalkan aspek-aspek baru tentang hubungan antara kebebasan individu dan teknologi. Teknologi digital dan media sosial sangat berpengaruh dalam kehidupan sehari-hari, komunikasi antara keluarga dan teman tidak dibatasi oleh tantangan geografis. Media sosial memudahkan mengekspresikan dan memahami diri kita sendiri melalui komunitas online. Penelitian ini bertujuan untuk melihat bagaimana self-representasi di era digital yang ditunjukan dalam acara TV Black Mirror episode Nosedive karya Charlie Brooker. Penulis melakukan analisis semiotika pada episode pertama di Musim 3, "Nosedive," mengenai self-representasi yang ditunjukan dan bagaimana hubungan yang diciptakan terhadap melalui media sosial dalam semua hubungan Lacie Pound. Terobsesi dengan peringkat sosial Lacie harus melakukan interaksi positif dan merepresentasikan dirinya sesuai dengan standar sosial. Peringkat nilai dalam Nosedive membuat hubungan antar masyarakat menjadi palsu karena mereka mementingkan penilaian yang diberikan satu sama lain. Semua masyarakat dalam dunia itu harus mengikuti standar sosial yang ada atau mereka dapat diasingkan karena memiliki penilaian yang rendah. Nosedive meniru masalah kontemporer obsesi prestasi sosial melalui pengasingan kognitif, yang menceritakan kegembiraan mereka saat ini dengan konektivitas digital dan sosial. Penelitian ini menggunakan teori semiotika Charles Sanders Pierce dengan pendekatan penelitian metode kualitatif. Peneliti mengumpulkan data dengan observasi dan dokumentasi, studi pustaka dan sumber online.